مفهوم الابتكار في الإسلام ومنهجية تطبيقه في المؤسسات المعاصرة الامارات نموذجاً: The concept of innovation in Islam and the methodology of its application in contemporary institutions, the UAE as a model - Alhosani, Badr Ramadan; Al-tahitah, Ali Nasser (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص إن الإسلام شرع للابتكار من خلال الاجتهاد والإبداع الفكري، وأنه يمنع من الجمود والتقليد الأعمى غير المبني على الحجج والبراهين، فقد شرع الإسلام للاجتهاد والابتكار لمواكبة مستجدات الحياة المعاصرة باعتباره صالحاً لكل زمان ومكان من خلال الموازنة بين ثبات النصوص الشرعية وقدسيتها، وبين الحاجة إلى الابتكار والتجديد لتلبية الاحتياجات المتنوعة في كل الأزمنة والعصور. وقد أثبتت الدراسات المتخصصة أن الاجتهاد والابتكار الفكري من أصول الدين، وأن علماء الإسلام في الأزمنة المعاصرة قادرون على تقديم الحلول العلمية لمشكلات العالم المعاصر استناداً إلى منهج أسلافهم، إذا استوعبوا تاريخهم وسلكوا طريقهم، كما أثبتت الفضل الكبير للحضارة الإسلامية على حضارة العالم شرقاً وغرباً ابتداءً من القيم والأخلاق، ومروراً باللغة والآداب، وانتهاءً بالعلوم التطبيقية والاختراعات المعاصرة. إن للابتكار مجالات شتى في جميع مرافق الحياة، فكما يكون في البرمجيات والميكانيكا والاتصال والفضاء والدفاع؛ يكون كذلك في النُظم الإدارية وإسعاد الناس وإخراجهم من الأساليب العقيمة المعقدة التي لا معنى لها إلا ضياع الوقت والجهد، والتي يؤسف أنها لاتزال في بعض المؤسسات الحكومية. وإن الإمارات لديها قيادة حكيمة تؤمن بأن الابتكار هو رأس مال المستقبل وبأن بناء الإنسان يأتي قبل رفع البنيان، ولذلك فهي تؤمن بأن العلم والمعرفة هي أهم أصولها وبأن إبداع الإنسان هو سر حضارتها وبأن الانفتاح على جميع حضارات العالم هو مفتاح قوتها. وقد جعلت دولة الإمارات جعلت من الابتكار قيمة مضافة لها وزنها في الاقتصاد الوطني وفي المجتمع ككل، حيث أن الابتكار لم يعد خياراً، وإنما هو ضرورة للدول والمجتمعات والشعوب الساعية لتعزيز موقعها على خريطة العالم الاقتصادية وتقوية تنافسيتها. ولذلك فإن الإمارات وضعت الابتكار أحد المحاور الأساسية لرؤيتها 2021. إن الميزانية الضخمة التي أعلن عنها صاحب السمو الشيخ محمد بن راشد للابتكار، تؤكد عبقرية هذا القائد في جعل الابتكار نمط حياة، فلم يُبق عذراً لما كان يتردد من عدم وجود ميزانية كافية للبحث العلمي مقارنة بما تبذله الدول المتقدمة في هذا المجال، فها هي الميزانية الوفيرة، والتوجه السياسي الرسمي، والتفاعل الكبير من كل المؤسسات الحكومية والخاصة، فلم يبقَ إلا الجهد الذاتي من الناس على اختلاف تخصصاتهم، فعلى كل واحد ألا يستقل نفسه، فلعله يجود بفكرة تكون سبباً لنفع كبير. Abstract Islam has legalized innovation through intellectual diligence and creativity, and it prevents rigidity and blind imitation that is not based on arguments and proofs. Islam has legalized for ijtihad and innovation to keep pace with the developments of contemporary life as it is good for every time and place by balancing the stability and sanctity of legal texts, and the need for innovation and renewal to meet the diverse needs of all times and ages. Specialized studies have proven that diligence and intellectual innovation are the origins of religion, and that the scholars of Islam in contemporary times are able to provide scientific solutions to the problems of the contemporary world based on the approach of their predecessors, if they absorbed their history and followed their path, as it proved the great merit of Islamic civilization over the civilization of the world east and west starting from Values and ethics, passing through language and literature, and ending with applied science and contemporary inventions. Innovation has various fields in all facilities of life, as it is in software, mechanics, communication, space and defense; It is the same in administrative systems, making people happy, and removing them from sterile, complex methods that have no meaning except waste of time and effort, which is unfortunately still in some governmental institutions. The Emirates has a wise leadership that believes that innovation is the capital of the future and that building the human comes before lifting the structure, and therefore it believes that science and knowledge are the most important assets and that human creativity is the secret of their civilization and that openness to all civilizations of the world is the key to its strength. The UAE has made innovation an added value that has its weight in the national economy and in society as a whole, as innovation is no longer an option, but rather a necessity for countries, societies and peoples seeking to enhance their position on the world economic map and strengthen their competitiveness. Therefore, the UAE has put innovation as one of the main axes of its vision 2021. The huge budget announced by His Highness Sheikh Mohammed bin Rashid for innovation confirms the genius of this leader in making innovation a lifestyle, so he did not remain an excuse for what was rumored of not having a sufficient budget for scientific research compared to what The developed countries exert it in this field, as it is the abundant budget, the official political orientation, and the great interaction of all governmental and private institutions, so only the self-effort of people of different specialties remains, so that each one does not resign himself, so perhaps he finds an idea that is a reason for great benefit .